2019
DOI: 10.1055/s-0039-1688500
|View full text |Cite
|
Sign up to set email alerts
|

Does Component Alignment Affect Patient Reported Outcomes following Bicruciate Retaining Total Knee Arthroplasty? An In Vivo Three-Dimensional Analysis

Abstract: AbstractThis is an experimental study. Anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) retaining bicruciate retaining (BCR) total knee arthroplasty (TKA) have the potential to restore normal knee kinematics and thus improve patient outcome. Limited studies have examined the relationship between component alignment and patient-reported outcome measures (PROM). This study aims to determine (1) accurate three-dimensional (3D) component alignment of BCR TKA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
(23 reference statements)
2
18
0
Order By: Relevance
“…This suggests that one of the important aspects during contemporary BCR TKA is to avoid increased PTS to reduce an excessive loading of ACL. This is in concordance with a recent in vivo kinematic study, 18 demonstrating that PTS is negatively correlated with the Knee Society Score in patients with contemporary BCR TKA, suggesting that this may be associated with excessive stresses in the ACL. An in vivo kinematic analysis with 29 CR TKA patients by Fujimoto et al demonstrated that an increased PTS generated a greater posterior force on the femur during weight-bearing knee flexion, 43 illustrating that without the ACL, this force shifts the femur posteriorly into an equilibrium position.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that one of the important aspects during contemporary BCR TKA is to avoid increased PTS to reduce an excessive loading of ACL. This is in concordance with a recent in vivo kinematic study, 18 demonstrating that PTS is negatively correlated with the Knee Society Score in patients with contemporary BCR TKA, suggesting that this may be associated with excessive stresses in the ACL. An in vivo kinematic analysis with 29 CR TKA patients by Fujimoto et al demonstrated that an increased PTS generated a greater posterior force on the femur during weight-bearing knee flexion, 43 illustrating that without the ACL, this force shifts the femur posteriorly into an equilibrium position.…”
Section: Discussionsupporting
confidence: 92%
“…Posterior tibial slope (PTS), defined as the posterior inclination of the tibial plateau, represents an important surgical implant alignment parameter in patients with TKA, with increased PTS being associated with significant alterations in in vivo knee joint biomechanics, inferior patientreported outcome measures (PROMs) as well as an increased injury risk. 17,18 Despite published articles on the effect of PTS on ACL extension in native knees, [19][20][21] there is a paucity of data on the potential effect of posterior slope of the tibial implant on elongation and stress experienced by the retained ACL in BCR TKA designs. Therefore, the aim of this study is to investigate the in vivo effect of PTS on stress experienced by the retained ACL during weight bearing STS and single-leg deep lunge in BCR patients.…”
mentioning
confidence: 99%
“…Despite so, as reported by Peng et al [ 38 ] in his 3D component orientations analysis relevant variations in component position were observed, especially for the tibial component, using standard instrumentation. Moreover, those variations, especially regarding tibial slope, where related to the 1-year clinical outcomes obtained.…”
Section: Technical Featuresmentioning
confidence: 76%
“…There was a lower extension angle of UKA knees than healthy and BCR TKA knees ( P < 0.01), lower flexion angle of BCR TKA knees than healthy and UKA knees ( P < 0.01), and lower flexion angle of UKA knees than healthy knees ( P < 0.01). Peng et al [ 38 ] examined the relation between component alignment and patient reported outcome measures (PROMs) in 29 BCR TKA implants [Vanguard XP Total Knee System (Zimmer Biomet)]. At 1-year follow-up, they verified a significant overall postoperative improvement in KSS (8.1 ± 11.8 preoperative to 87.9 ± 16.7 postoperative, P < 0.001).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…However, this represents a common limitation of studies on this research. 34,35 In conclusion, despite the replication of native knee flexion/extension by the contemporary asymmetrical bearing geometry CR TKA design with concave medial and convex lateral tibial polyethylene bearing components, asymmetric knee motion persisted in in vivo unilateral CR TKA patients during strenuous knee flexion activities and gait. Further studies are required to investigate the potential effects of implant designs, component positioning, and patient factors in optimizing in vivo kinematics of CR TKA during gait and functional daily activities.…”
Section: Discussionmentioning
confidence: 89%